New alliances around the birth - de Francesco, Laura; Monini, Tullio (Rivista Italiana di Educazione Familiare, 2011)
The article demonstrates the two decades experience and commitment of the Center for Families of Ferrara in the field of parenting support and services dedicated to children and parents before and after birth. The basic choice of the Centre, which is one of the first born in Italy, was the creation of a real friendly network of families in order to help parents to develop their educational and personal skills. This choice is well represented in the last project created to prevent and support fragile families in the period before and after birth: the Counselor’s Point “Welcome…my little one!”, that represents the result of active and intense collaboration between several professionals and between various municipal and health services.